2001
DOI: 10.1038/nsb0901-789
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Homologs of the Escherichia coli surE gene are present in many eubacteria and archaea. Despite the evolutionary conservation, little information is available on the structure and function of their gene products. We have determined the crystal structure of the SurE protein from Thermotoga maritima. The structure reveals the dimeric arrangement of the subunits and an active site around a bound metal ion. We also demonstrate that the SurE protein exhibits a divalent metal ion-dependent phosphatase activity that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(68 citation statements)
references
References 26 publications
2
66
0
Order By: Relevance
“…Our biochemical studies of the E. coli SurE and the previous data on two SurE proteins from the thermophilic bacterium Thermotoga maritima (17,38) and from the archaebacterium Pyrobaculum aerophilum (39) clearly demonstrated that the annotation of SurE proteins as acid phosphatases is not accurate. Acid phosphatases (EC 3.1.3.2) comprise a large group of nonspecific phosphohydrolases capable to hydrolyze a broad range of phosphorylated sugars, amino acids, nucleoside mono-, di-, and triphosphates (BRENDA data base, www.brenda.uni-koeln.de/).…”
Section: Screening Of Purified Proteins For Phosphatase Activity-mentioning
confidence: 94%
See 1 more Smart Citation
“…Our biochemical studies of the E. coli SurE and the previous data on two SurE proteins from the thermophilic bacterium Thermotoga maritima (17,38) and from the archaebacterium Pyrobaculum aerophilum (39) clearly demonstrated that the annotation of SurE proteins as acid phosphatases is not accurate. Acid phosphatases (EC 3.1.3.2) comprise a large group of nonspecific phosphohydrolases capable to hydrolyze a broad range of phosphorylated sugars, amino acids, nucleoside mono-, di-, and triphosphates (BRENDA data base, www.brenda.uni-koeln.de/).…”
Section: Screening Of Purified Proteins For Phosphatase Activity-mentioning
confidence: 94%
“…In HAD-like phosphohydrolases, the metal cofactor (usually Mg 2ϩ ) is involved in the coordination of the nucleophilic side-chain carboxylate of catalytic Asp and the phosphoryl group of the substrate (36,37). Recent structural studies of SurE proteins from T. maritima and P. aerophilum revealed the presence in the active site of mononuclear metal center chelated by several conserved residues, including the strictly conserved N-terminal DD pair (17,38,39). The threedimensional structure of the N-terminal fragment of the bifunctional Rel/Spo homologue (the HD domain protein) from Streptococcus dysgalactiae identified several conserved residues (His-53, His-77, Asp-78, and Asp-144) involved in the coordination of Mn 2ϩ (40).…”
Section: Screening Of Purified Proteins For Phosphatase Activity-mentioning
confidence: 99%
“…As the three-dimensional structure of proteins is intimately coupled with the molecular function, the structure of a protein may provide clues for its molecular function. The validity of this approach has been demonstrated by several examples (1)(2)(3), and a number of large-scale structural genomics projects have been initiated (4,5).…”
mentioning
confidence: 99%
“…The predictions can provide a basis for assigning a molecular function to the hypothetical protein. For instance, Zarembinski et al (1998), Hwang et al (1999) and Lee et al (2001) have succeeded in structure-based assignment of the molecular function of hypothetical proteins. The overall conformation, detection of the active site and the amino-acid composition of the active site, which can be revealed from the structure of YedU, would lead us to the elucidation of its biochemical function.…”
Section: Introductionmentioning
confidence: 99%